CONCEPT OF DEVELOPMENT OF PUBLIC EDUCATION IN SOVIET RUSSIA IN THE TWENTIES OF THE TWENTIETH CENTURY - Alexey V. Bogachev; Liudmila B. Zakharova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2015)
The article is devoted to the most important stage of the formation of the Soviet state subject - development of a system of universal and affordable public education. The beginning was the Decree of the "unified labor school", proclaimed the new principles and methods of teaching and educational activity of the Soviet school and formed a unified school system. The main principle of the school was named labor training, socially useful, productive labor. The idea of collective work, "school commune" was aimed at the education of future citizens. Soviet pedagogy was aimed at ensuring free and compulsory general and polytechnical education for all children up to 17 years, extensive development of vocational training for people over 17 years of age. The 1920s were marked by active searches in the theoretical development of school curricula and teaching methods of disciplines up to the radical revolutionary experiments with the school. However, by the end of the 1920s experimental pedagogy was ousted unification of curricula, began the formation of the state policy in the field of education.